The Stimulus Factors for The Study of The Qur'an in Learning Tajwid SD/MI - Vivin Devi Prahesti (Proceeding International Conference on Religion, Science and Education, 2023)
This study aims to determine the stimulus factors for the study of the Qur'an in learning tajwid SD/MI. This type of research is a literature study with a qualitative research approach. This data collection technique is the documentation of several sources of relevant books and journals. The data analysis technique of this research is to use descriptive analysis. The findings of this study are that the motivating factor for students to learn tajwid is that they have a desire to learn the laws of reciting the Qur'an. The researcher concluded that the thing that encourages students to learn the Qur'an is to reduce mistakes in reading the Qur'an through the science of recitation. Thus the driving factors for the study of the Qur'an can be a reference for educators in learning tajwid as a basis for reading the Qur'an.